2017
DOI: 10.5603/cj.a2016.0070
|View full text |Cite
|
Sign up to set email alerts
|

Association of factor XIII Val34Leu polymorphism and coronary artery disease: A meta-analysis

Abstract: (Cardiol J 2017; 24, 1: 74-84)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Coronary artery disease (CAD), as the most common etiology of heart attack and death in the world, is a multifactorial disease caused by the combined impact of genes [1]. The main etiology of CAD is characterized by defective endothelial function; however, the underlying mechanism has not been fully elucidated despite the high incidence of CAD [2].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD), as the most common etiology of heart attack and death in the world, is a multifactorial disease caused by the combined impact of genes [1]. The main etiology of CAD is characterized by defective endothelial function; however, the underlying mechanism has not been fully elucidated despite the high incidence of CAD [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although the modified fibrin phenotype seems to be related to premature CAD, there was no association between the F13A1 Val34Leu genetic variant and MI in young patients in other studies [22, 23]. Nevertheless, the most recently published meta-analysis revealed that F13A1 Val34Leu variant was associated with CAD risk, especially MI, without differences in age [24].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic determinants of fibrin clot properties have naturally been sought as a means of risk stratification and to identify possible treatment targets. Focus points have been the FXIII Val34Leu and PAI-1 4G/4G polymorphisms which have both been linked to CAD risk in large meta-analyses [15,16]. However, the association between these genetic variants and CAD is modest in size and is dependent on other factors, mainly fibrinogen, and the potential mechanisms through which these polymorphisms may influence fibrin clot structure are also not clear [17].…”
Section: Fibrin Clot Propertiesmentioning
confidence: 99%